Strength Training Modulates Prostate of Wistar Rats Submitted to High-Fat Diet - Veras, Allice Santos Cruz [UNESP]; de Freitas, Marcelo Conrado [UNESP]; Thorpe, Hayley Hope Allyssa; Seraphim, Patrícia Monteiro [UNESP]; Teixeira, Giovana Rampazzo [UNESP] (Springer Nature, 2020)
Our aim is to evaluate the effects of high-fat diet and strength training on ventral prostate health through investigations of rat prostate histology, endocrine modulation, and the expression of proliferative and apoptotic marker, including androgen receptors (AR), glucocorticoid receptors (GR), B-cell lymphoma 2 (Bcl-2), Bcl-2 associated X protein (BAX), Fas cell surface death receptor (Fas/CD95/Apo-1), and Nuclear Factor Kappa-B (NF-κB). Eighty Wistar rats were into one of four subgroups: control (CT), strength training (ST), high-fat diet consumption (HF), and high-fat diet consumption with strength training (HFT). Animals then underwent strength training and/or high-fat diet consumption for 8 or 12 weeks, after which animals were euthanized and markers of prostatic health were evaluated histologically and through immunolabeling. Our results indicate that physical strength training reduced the expression of the prostate cell proliferation marker Bcl-2 while increasing expression of the pro-apoptotic marker BAX, as well as increasing expression of AR and GR relevant in the Bcl-2 pathway. We conclude that a high-fat diet can alter hormone receptor levels and cell-cycle protein expression, thereby modifying prostatic homeostasis, and that strength training was able to reduce prostate damage induced by high-fat diet consumption.
Keywords: Apoptosis pathway; Inflammation; Physical exercise; Prostate health